2007
DOI: 10.1002/ccd.21169
|View full text |Cite
|
Sign up to set email alerts
|

Transradial approach for noncoronary angiography and interventions

Abstract: The transradial approach was useful for non-coronary angiography and interventions and offers the advantages of low risk and reduced stress on patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 52 publications
2
15
0
3
Order By: Relevance
“…A few observational studies, feasibility studies, technical reports, case series, and case reports have demonstrated successful application of TRA for addressing peripheral arterial disease (PAD) including internal carotid, vertebral and basilar, subclavian and innominate, renal, iliac, celiac, mesenteric, and superficial femoral artery lesions [117–126]. Importantly, TRA provides an alternative to the femoral approach in patients with severe lower limb and/or aortoiliac vascular disease.…”
Section: Peripheral Applicationsmentioning
confidence: 99%
“…A few observational studies, feasibility studies, technical reports, case series, and case reports have demonstrated successful application of TRA for addressing peripheral arterial disease (PAD) including internal carotid, vertebral and basilar, subclavian and innominate, renal, iliac, celiac, mesenteric, and superficial femoral artery lesions [117–126]. Importantly, TRA provides an alternative to the femoral approach in patients with severe lower limb and/or aortoiliac vascular disease.…”
Section: Peripheral Applicationsmentioning
confidence: 99%
“…In the registry from Leipzig [42] the incidence of RAO during hospitalization was evaluated and was as follows: for 5 Fr sheaths 13.7%, and for 6 Fr sheaths up to 30.5%. Nagai underlines the usefulness of radial artery diameter assessment by Doppler before cannulation, in finding the right equipment [57]. In this study, the ratio of the sheath diameter to the radial artery diameter > 1 was associated with a higher risk of RAO (38% vs. 14%, p < 0.01).…”
Section: Prevention Of Radial Artery Occlusionmentioning
confidence: 58%
“…Radial artery occlusion is frequently observed in women, which is associated with a smaller diameter of the radial artery and its greater predisposition to contraction [56]. Additionally, the presence of diabetes [57], peripheral arterial disease [58] and smoking [36] are predictors of this complication.…”
Section: Predictors Of Radial Artery Occlusionmentioning
confidence: 99%
“…Mesmo em áreas antes indiscutíveis do acesso femoral, como no estudo de enxertos arteriais e venosos após cirurgia de revascularização do miocárdio 5 e para o diagnóstico e intervenção não-coronária 6 , a via radial tem sido utilizada com a manutenção dos resultados e diminuição das complicações, apesar da necessidade de se ultrapassar a curva de aprendizagem 7 .…”
Section: Discussionunclassified